2021
DOI: 10.1093/eurheartj/ehaa1103
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and clinical outcomes in patients with COVID-19

Abstract: Background A systemic inflammatory response is observed in coronavirus disease 2019 (COVID-19). Elevated serum levels of C-reactive protein (CRP), a marker of systemic inflammation, are associated with severe disease in bacterial or viral infections. We aimed to explore associations between CRP concentration at initial hospital presentation and clinical outcomes in patients with COVID-19. Methods and results Consecutive adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
273
4
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(315 citation statements)
references
References 30 publications
25
273
4
13
Order By: Relevance
“…Han et al found that serum LDH and CRP were signi cantly correlated with the severity of COVID-19. And Smilowitz NR et al also came to the conclusion that CRP was strongly associated with critical illness and mortality in COVID-19 [44]. In our study, CRP elevation appeared to be higher in the severe/critical group than in the moderate group (P = 0.076).…”
Section: Discussionsupporting
confidence: 66%
“…Han et al found that serum LDH and CRP were signi cantly correlated with the severity of COVID-19. And Smilowitz NR et al also came to the conclusion that CRP was strongly associated with critical illness and mortality in COVID-19 [44]. In our study, CRP elevation appeared to be higher in the severe/critical group than in the moderate group (P = 0.076).…”
Section: Discussionsupporting
confidence: 66%
“…Inflammation may also trigger arrhythmias through determining a more severe clinical course of COVID-19. Inflammatory burden during COVID-19 was associated with greater disease severity [ 59 ] and increased risk of death [ 60 ]. On the other hand, the association between critically ill status and the onset of AF is well established, particularly during infections [ 7 ]; indeed, AF in our study was associated with a five-fold greater chance of having a critical clinical state.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies identified an association between the novel coronavirus disease 2019 (Covid- 19), inflammation, hypercoagulability, and thrombosis. [1][2][3][4] Critically ill patients with Covid-19 are at high risk of venous and arterial thrombotic events despite standard dose pharmacological thromboprophylaxis. [5][6][7][8] Higher levels of circulating biomarkers reflecting systemic inflammation and coagulation activation (e.g., D-dimer, C-reactive protein) are independently associated with a greater risk of respiratory failure, thrombosis, and death.…”
Section: Introductionmentioning
confidence: 99%